HUBUNGAN FAKTOR INTERNAL DAN FAKTOR EKSTERNAL IBU DALAM PEMBERIAN ASI EKSKLUSIF DI KELURAHAN PEKAN BAHOROK KECAMATAN BAHOROK KABUPATEN LANGKAT TAHUN 2014 - Ayu Yulia Ningsih Sirait; Ria Masniari Lubis; Erna Mutiara (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
ABSTRACTThe most perfect of baby’s nutrition is breastfeeding, because breastfeeding is the best natural nutrition for baby. The decrease of exclusive breastfeeding in Indonesia was caused by two factors, namely internal factors that included knowledge, behavior and physical factor, and external factors included family support, culture and integrated service post (Posyandu).The objective of the research was to know correlation between internal factors and external factors for mothers in giving exclusive breastfeeding at the Pekan Bahorok village in 2014. The type of research was analytic survey with cross sectional design. The population of the research were all mothers that had babies aged 7-12 months and ever giving breastfeeding on their babies as many as 58 mothers and all population were become sample by using test of data analyzing chi-square at α=0,05.The research result showed that 18 respondents (31.0%) were giving exclusive breastfeeding. There was a correlation between behavior (p<0.001), family support (p=0.012), culture (p<0.001) and integrated service post (p=0.017) with giving exclusive breastfeeding except knowledge and physical factor.It was suggested to the midwife for not directly to give formula milk to the babies when they were birth. And also to the Pekan Bahorok health centre to be more diligent to give information either in integrated service post (Posyandu) or moslem women organization so that mother and family can more receive and change the behavior more positive and it also can change the wrongness exclusive breastfeeding customs.Key Words : Exclusive Breastfeeding, Knowledge, Behavior, Physical Factor, Family Support, Culture, Integrated Service Post